2021
DOI: 10.1016/j.bbabio.2020.148337
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the catalytic mechanism of type VI sulfide:quinone oxidoreductases

Abstract: Sulfide oxidation is catalyzed by ancient membrane-bound sulfide:quinone oxidoreductases (SQR) which are classified into six different types. For catalysis of sulfide oxidation, all SQRs require FAD cofactor and a redoxactive centre in the active site, usually formed between conserved essential cysteines. SQRs of different types have variation in the number and position of cysteines, highlighting the potential for diverse catalytic mechanisms. The photosynthetic purple sulfur bacterium, Thiocapsa roseopersicin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 53 publications
(150 reference statements)
0
11
0
1
Order By: Relevance
“…S5). Likewise, previously published TrSqrF variants (Duzs et al 2021), a weak additional absorbance peak at 408 nm was observed in the UV-Vis spectra of these TrSqrF mutants, indicating the presence of trace amounts of c-type cytochromes in the samples (the extinction coefficient of heme-containing c-type cytochromes at 408 nm is high (170 mM −1 cm −1 ) (Sousa et al 2017;Sena et al 2018). The amount of c-type cytochrome contamination in SDS-PAGE is less than the detection limit (Fig.…”
Section: Spectroscopic Analysis Of Quinone Biding Site Mutant Trsqrf ...mentioning
confidence: 94%
See 4 more Smart Citations
“…S5). Likewise, previously published TrSqrF variants (Duzs et al 2021), a weak additional absorbance peak at 408 nm was observed in the UV-Vis spectra of these TrSqrF mutants, indicating the presence of trace amounts of c-type cytochromes in the samples (the extinction coefficient of heme-containing c-type cytochromes at 408 nm is high (170 mM −1 cm −1 ) (Sousa et al 2017;Sena et al 2018). The amount of c-type cytochrome contamination in SDS-PAGE is less than the detection limit (Fig.…”
Section: Spectroscopic Analysis Of Quinone Biding Site Mutant Trsqrf ...mentioning
confidence: 94%
“…The initial structure of the TrSqrF molecular dynamics (MD) calculations was the homology model previously described (Duzs et al 2021), in which the type VI SQR enzyme associated with dUQ and FAD cofactors was determined based on the crystal structures of A. ambivalens SqrE (Brito et al 2009) and A. aeolicus SqrA (Marcia et al 2010b). MD calculations were performed using the Desmond package (Schrödinger Release 2021-1) (Bowers et al 2006) of the Schrödinger software suites applying the OPLSA2005 (Jorgensen et al 1996) force field in combination with the SPC explicit water model.…”
Section: In Silico Analysis Of Protein-ligand Interactionsmentioning
confidence: 99%
See 3 more Smart Citations